Evaluation of tensile strength of Brazilian test under solid and ring disks using finite element analysis - Rini Asnida Abdullah; Takashi Tsutsumi (Penerbit Universiti Kebangsaan Malaysia, 2018)
The tensile strength of intact rock materials has been determined by indirect method more frequent than the direct method. The most commonly used indirect method is Brazilian test. Stress and deformability undergo during the test reflected by geometry shape of the samples with respect to the different diameter ratio. This study focuses on influence of geometry shape in solid and ring disk with different diameter ratio on the stress distribution and deformations within sandstone subjected to indirect tensile loading by Brazilian test. Then, the finite element method in RS2 software was utilised to simulate and gain in depth understanding the behaviour of Brazilian test. The analysis shown that the maximum tensile strength in a ring disk with diameter ratio of 0.1 is three times higher than in solid disk. Meanwhile, as the diameter ratio of ring disk increases, it produces lower tensile strength. The numerical simulation also has successfully illustrated the shear failure which observed near the loading platen of solid disk during Brazilian test. The finite element analysis utilised in this research has successfully enables the stress distribution and deformation behaviour of the rock under tension to be studied closely.